DEMOGRAPHIC SITUATION IN THE NORTHERN CAUCASUS: CURRENT STATE AND FUTURE PROSPECTS - SIGAREVA, Evgeniya; SIVOPLYASOVA, Svetlana; RYAZANTSEV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2019)
The paper examines the current state and future prospects of the demographic sphere in the North Caucasian regions. It determines probable trends in the region's demographic development based on statistical analysis. The sociological aspect of the study evaluates how the younger generation's paradigms of matrimonial, reproductive, and migration-related behavior are formed.Research demonstrates that the Northern Caucasus regions currently exhibit, and will continue to maintain, relatively high demographic indicator values compared to other constituents of the Russian Federation. However, positive dynamics in demographic growth are expected to slow down in this region as well. The results of the sociological poll reveal that a complete multi-child family remains the prevailing paradigm among youth in the Northern Caucasus. Nonetheless, the transformation of young people's concepts regarding family formation and childbearing is becoming increasingly apparent, especially in the region's major cities. These developments should raise concern in both scientific and political circles and be taken into account when forming and implementing demographic policy measures.